Molecular Epidemiology, Genetic Diversity, and Antifungal Susceptibility of Major Pathogenic Dermatophytes Isolated From Human Dermatophytosis - Salehi, Zahra; Shams-Ghahfarokhi, Masoomeh; Razzaghi-Abyaneh, Mehdi (Frontiers in Microbiology, 2021)
Background- Dermatophytes are a homogeneous group of species with low genetic diversity and there are still many uncertainties about the boundaries among species. Objectives- Aiming at clarifying the relationships among species in the genus and introducing suitable genes for multilocus sequence typing (MLST), a new MLST scheme approach was developed to characterize the major pathogenic dermatophytes. Methods- We performed maximum parsimony, MrBayes, RAxML, and eBURST analyses, based on the MLST scheme to scrutinize the evolution within 95 clinical isolates and 4 reference strains belonging to the four major dermatophytes species. Then, the discriminatory power, pairwise genetic distances, ratio dN/dS, and sequence types (STs) of these isolates were determined. Also, to study taxonomy, sequences of the ITS, BT2, and TEF-1α genes of other dermatophytes species available in GenBank were analyzed. Results- Findings of the present study indicated that three genes BT2, ITS and TEF‐1α which showed the greatest diversity among dermatophyte species were suitable for MLST. The most prevalent sequence types were seen among the species of Trichophyton interdigitale. Also, two new genotypes, i.e., XXVII and XXVIII were introduced for T. interdigitale and T. mentagrophytes. The least informative sites were found in E. floccosum, T. rubrum, and T. mentagrophytes, while the most informative sites were observed in T. interdigitale. Furthermore, the most informative locus was TEF-1α. The phylogenetic tree, constructed by the combination of the three genes, shows a new topological pattern that confirms the derivation of the anthropophilic and zoophilic genera from the geophilic genus. Also, the phylogenetic analyses and pairwise distances of the combination of the three loci showed that T. tonsurans and T. equinum was a species complex, where T. equinum is derived from T. tonsurans. Conclusions- Results of this study showed that MLST is very effective in determining the boundaries between species and taxonomy. Considering that there is no database for MLST dermatophytes, further studies are needed to determine the suitable genes for MLST. Also, the determination of STs in epidemiological studies and raising epidemiological information is helpful. This study was a new starting point to determine the ST and a foundation for a dermatophyte MLST database.